Effect of probiotic administration in adult atopic dermatitis patients: An evidence-based case report - Paramita, Dewita Nina Paramita; Sutanto, Krisadelfa (World Nutrition Journal, 2024)
Introduction: Atopic dermatitis (AD) is a chronic skin disease characterized by abnormal skin barrier function and heightened immunologic sensitization. Its incidence has surged recently, with approximately 60% of cases diagnosed within the first year of life. AD can persist or recur, significantly deteriorating the quality of life due to persistent itching and sleep disturbances. Individuals with AD are at increased risk of developing other atopic disorders like asthma and allergic rhinitis. Various dietary approaches, including low carbohydrate, calorie, and fat diets, have been associated with enhanced quality of life by regulating immune responses. Probiotics have been used as adjuvant therapy in allergic conditions, though their effectiveness varies due to the complex nature of allergies. Method: A literature search was conducted using PubMed, Cochrane Library, and Google Scholar. MeSH terms, advanced search strategies, and predefined eligibility criteria were employed to identify relevant studies. Duplicate studies were excluded, and critical assessment tools and levels of evidence were defined per Oxford Center for Evidence-based Medicine standards. Results: One systematic review and meta-analysis of randomized controlled trials (RCTs) met the PICO and eligibility criteria. The meta-analysis demonstrated that probiotics significantly decreased AD severity in adults, enhancing their overall quality of life. Other meta-analyses and systematic reviews supported that probiotics reduce clinical severity and improve life quality in adult AD patients. Conclusion: Probiotic supplementation is a viable option to improve the quality of life for adult AD patients, offering potential therapeutic benefits in managing this condition.